P381 A CHALLENGING PACEMAKER IMPLANTATION IN THE PRESENCE OF A GIANT RIGHT CORONARY ANEURYSM COMPRESSING THE RIGHT ATRIUM. (18th May 2022) - Maffè, S; Paffoni, P; Bergamasco, L; Facchini, E; Prenna, E; Careri, G; Franchetti Pardo, N; Paino, A; Dellavesa, P
Abstract: Giant coronary artery aneurysm is an uncommon disease, treated with surgerical intervention or percutaneous coil embolization. A thrombosed aneurysm can cause extrinsic compression on the cardiac chambers, with potential haemodynamic effects and may cause problems when we need to implant a cardiac device. We present a 85–year–old patient, with a previous myocardial infarction and double coronary artery bypass graft in 1995. In 2013 he was hospitalized for heart failure and severe mitral insufficiency, with cardiac surgery indication. Preoperative coronary angiography revealed a giant right coronary aneurysm (65x75mm). The aneurysm was partially thrombosed and in close contact with the posterior sternal wall; it was decided to treat it by coil embolization in order to avoid damage during the initial stages of cardiac surgery (sternotomy and isolation of the pericardium). Subsequently, the replacement of the mitral valve with a bioprosthesis was performed without complications. In 2019 a chest CT scan, in an asymptomatic patient, showed an enlarged coronary aneurysm (85x90mm), completely thrombosed, compressing the right atrium, for which a conservative approach was maintained. The patient was hospitalized in May 2021 following 3 syncopes, with cranial trauma. The EKG shows sinus rhythm with first degree AV block and complete left bundle branch block. Chest CT confirmed the aneurysm, unchanged from 2019 (Fig 1 ). Transthoracic and transesophageal echocardiography confirmed compression of the mass on the right atrium, reduced to a very small cavity (Fig 2 ). A stress echocardiogram with dobutamine, performed to evaluate a possible hemodynamic effect of atrial compression, showed no changes in diastolic ventricular filling, arrhythmias, pressure drops, or significant symptoms. Based on these assessments, the syncopes and EKG changes, we implanted a VVIR ventricular pacemaker. The procedure was hampered by the difficulty of passing the lead through the compressed right atrium in order to reach the tricuspid plane and then enter the right ventricle; only after numerous attempts, and with the help of simultaneous echocardiographic and fluoroscopic guidance, was it possible to complete the procedure without complications (Fig 3 ). This case demonstrates the usefulness of the echocardiogram, in particular contexts, in cardiac electro–stimulation procedure